Radiation exposure during endourologic procedures using over-the-table fluoroscopy sources - Ritter, Manuel; Krombach, Patrick; Martinschek, Andreas; Siegel, Fabian; Weiß, Christel; Häcker, Axel; Pelzer, Alexandre E. (Journal of endourology, 2012)
Background and Purpose: Fluoroscopy is used daily by endourologic surgeons worldwide without knowledge of received radiation doses. We wanted to assess the radiation exposure of endourologic surgeons by frequently performed endourologic interventions with an over-the-table x-ray system.Patients and Methods: In this prospective single-center study, 235 endourologic interventions in 188 patients from April to September 2010 were included. Sixty-seven ureteral stent placements (USP), 51 ureteral stent changes (USC), 67 percutaneous stent changes (PSC), 11 percutaneous nephrolithotomies (PCNL), and 39 ureterorenoscopies (URS) were performed by 12 surgeons. The surgeon`s radiation exposure was measured with one thermoluminescent dosimeter (TLD) at the forehead and one at the ring finger. TLDs were analyzed at a central institute. The radiation dose detected at the forehead was counted as representative for the lens of the eye and the thyroid.Results: Mean patient age was 60.6 (±18.8) years. Analysis of the TLD showed the following average values at the forehead for each intervention: USP and USC 0.04 mSv; PSC 0.03 mSv; PCNL 0.18 mSv; URS 0.1 mSv. Average finger values are: USP 0.13 mSv; USC 0.21 mSv; PSC 0.20 mSv; PCNL 4.36 mSv; URS 0.15 mSv.Conclusions: This report evaluates surgeons' radiation exposure by everyday endourologic interventions of different complexity. Most can be performed with an over-the-table x-ray system without exceeding statutory limits. Especially for PCNL, surgeons should consider possible protective action.
Published online:4 Jan 2012
Gesehen am 28.06.2018